SAT-LB85 Use of Weekly Levothyroxine Regimen for Rapid Normalization of Thyroid Hormone Levels: A Case Report - Escudero, Jose Renato Martinez (J Endocr Soc, 2020)
Background: Hypothyroidism affects around 4.6% of the U.S. population(1). Non-adherence with thyroid hormone replacement is one of the biggest challenges in treating hypothyroidism(1). The half-life of T4 and T3 in hypothyroidism is about 7.5 and 1.4 days respectively(2). A large dose once-weekly administration of levothyroxine (Lt4) is possible(3, 4). Recent publications suggest that once-weekly Lt4 does not increase the risk of cardiovascular events and is well tolerated by most of patients(4). Once weekly Lt4 produces similar results as daily Lt4 as evidenced by thyroid function tests(3,4), and potentially improves patient compliance and satisfaction with the treatment(4). Clinical Course: A 29-year-old female with a history of Hashimoto’s hypothyroidism, polycystic ovarian syndrome, depression, presented with irregular menses. Her symptoms included depression, fatigue, increased appetite. Her TSH was grossly elevated at 217 uIU/mL (0.27-4.20 uIU/mL). However upon re-visit, after increasing Lt4 to 100 mcg daily her TSH increased to 280 uIU/mL. She admitted to non-adherence with her daily Lt4 prescription. Physical exam was notable for sinus bradycardia and slow mentation, otherwise unremarkable. Blood count, basic metabolic panel and hemoglobin A1C were within normal limits. Liver function tests showed mild transaminitis, ALT 46 U/L (10-45 U/L). Lt4 was started at 875 mcg per week. At five weeks, her TSH was 6.31 uIU/mL and at seven weeks, the patient was euthyroid with a TSH of 2.53 uIU/mL. Her periods have since normalized. Conclusion: The current discourse on weekly dosing mainly focuses on its use for non-adherent patients. This case provides a clear time course also demonstrating rapid normalization of TSH using weekly dosing. Weekly Lt4 dosing as first-line therapy in noncompliant depressed patients with severe hypothyroidism should be considered. 1.Hepp, Z., Wyne, K., Manthena, S., Wang, S. and Gossain, V. (2018). Adherence to thyroid hormone replacement therapy: a retrospective, claims database analysis. Current Medical Research and Opinion, 34(9), pp.1673-1678.2.Colucci, P., Yue, C., Ducharme, M. and Benvenga, S. (2010). A Review of the Pharmacokinetics of Levothyroxine for the Treatment of Hypothyroidism. European Endocrinology, 9(1), p.40.3.Jayakumari, C., Nair, A., Puthiyaveettil Khadar, J., Das, D., Prasad, N., Jessy, S., Gopi, A. and Guruprasad, P. (2019). Efficacy and Safety of Once-Weekly Thyroxine for Thyroxine-Resistant Hypothyroidism. Journal of the Endocrine Society, 3(12), pp.2184-2193.4.Rajput, R. and Pathak, V. (2017). The Effect of Daily versus Weekly Levothyroxine Replacement on Thyroid Function Test in Hypothyroid Patients at a Tertiary Care Centre in Haryana. European Thyroid Journal, 6(5), pp.250-254.